Direct grafting poly(methyl methacrylate) from TiO2 nanoparticles via Cu2+‐amine redox‐initiated radical polymerization: An advantage of monocenter initiation. Issue 4 (15th May 2014) - Yao, Rongrong; Wu, Rong; Zhai, Guangqun
Abstract : Cu 2+ can oxidize amines to generate radicals to initiate radical polymerization of electron‐deficient monomers under mild conditions. Here, CuSO4 ‐catalyzed redox‐initiated radical polymerizations of methyl methacrylate from amino‐functionalized TiO2 nanoparticles (TiO2 ‐NH2 nanoparticles) was performed to prepare TiO2 nanoparticles grafted with poly(methyl methacrylate) (TiO2 ‐ g ‐PMMA hybrid nanoparticles) in dimethylsulfoxide or N, N ‐dimethylformamide at 90°C. Infrared spectroscopy, thermogravimetric analysis, and X‐ray photoelectron spectroscopy confirmed the presence of the grafted PMMA and the grafting yield was about 50 wt%. Microscopy and particle‐size analysis indicated that TiO2 ‐ g ‐PMMA nanoparticles had a good affinity to organic media. Because only aminyl radical (NH) on TiO2 nanoparticles formed in Cu 2+ ‐amine redox‐initiation step, there was no free PMMA chains formed during polymerization. Thus, our protocol provides a facile strategy to prepare inorganic/organic hybrid nanoparticles via one‐pot Cu 2+ ‐amine redox‐initiated free radical polymerization. POLYM. ENG. SCI., 55:735–744, 2015. © 2014 Society of Plastics Engineers